Two-component curable adhesive composition

By adopting a two-component curable adhesive composition, the combination of alkyl (meth)acrylate monomer, acrylonitrile-butadiene rubber and toughening agent is solved, and the structural adhesive is easily degraded when contacting human skin is achieved, achieving high chemical resistance and good mechanical properties.

CN119836457APending Publication Date: 2025-04-15HENKEL KGAA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202280099778.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-09-06
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing structural adhesives tend to deteriorate when they come into contact with human skin, and lack the means to effectively improve their chemical resistance.

Method used

Using a two-component curable adhesive composition, component A comprises alkyl (meth)acrylate monomer, acrylonitrile-butadiene rubber and toughening agent, component B comprises a catalyst, and the chemical resistance of the adhesive is improved by specific component ratios and combinations of additives.

Benefits of technology

Excellent chemical resistance during curing, especially oleic acid resistance, is achieved while maintaining mechanical properties and dispensability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005297500120000071
    Figure BDA0005297500120000071
  • Figure BDA0005297500120000081
    Figure BDA0005297500120000081
  • Figure BDA0005297500120000082
    Figure BDA0005297500120000082
Patent Text Reader

Abstract

The present invention provides a two-component curable adhesive composition consisting of a component A comprising: (a) at least one alkyl (meth) acrylate monomer, (b) at least one acrylonitrile-butadiene rubber wherein, based on the total weight of the acrylonitrile-butadiene rubber, the component A comprises at least one alkyl (meth) acrylate monomer, and the component B comprises at least one alkyl (meth) acrylate monomer, and (b) at least one acrylonitrile-butadiene rubber, based on the total weight of the acrylonitrile-butadiene rubber, based on the total weight of the acrylonitrile-butadiene rubber; (c) at least one acrylonitrile-butadiene rubber having an acrylonitrile content of less than 45% by weight, and (c) at least one toughening agent selected from the group consisting of polyester-based urethane (meth) acrylate oligomers and / or (meth) acrylate-terminated acrylonitrile-butadiene oligomers; and a component B comprising at least one catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a two-component curable adhesive composition and use thereof. Background Art

[0002] Structural adhesives are widely used for bonding substrates (such as metals, plastics, etc.) in manufacturing environments due to their fast curing speed and high impact resistance. Typically, structural adhesives are formed from two parts: a composition containing a curing agent (based on acrylate or methacrylate) and a catalyst for curing the adhesive. The two parts are stored in two different compartments and mixed before the application of the adhesive. This catalyst is a free radical polymer initiator, particularly peroxide-based, and is well known in the art. The part containing the curing agent also contains other ingredients, such as a curing accelerator, a rheology modifier, or an adhesion promoter. Such adhesives are particularly described in US2013 / 0292054 A1, US 6602958 B2, EP2194105 B1, etc.

[0003] When structural adhesives are used in handheld electronic devices, they may come into contact with human skin and be exposed to chemicals on the skin (e.g., sweat, oils, cosmetics, etc.), which may cause the performance of the adhesive to deteriorate. Few prior art techniques have been found to improve the chemical resistance of structural adhesives. Therefore, there is a need for a two-component curable adhesive composition that exhibits excellent chemical resistance (e.g., oleic acid resistance) when cured while maintaining mechanical properties and dispensability. Summary of the invention

[0004] According to a first aspect of the present invention, a two-component curable adhesive composition is disclosed herein, which consists of the following components:

[0005] Component A, comprising:

[0006] (a) at least one alkyl (meth)acrylate monomer,

[0007] (b) at least one acrylonitrile-butadiene rubber, wherein the acrylonitrile-butadiene rubber has an acrylonitrile content of less than 45% by weight, based on the total weight of the acrylonitrile-butadiene rubber, and

[0008] (c) at least one toughening agent selected from polyester-based urethane (meth)acrylate oligomers and / or (meth)acrylate-terminated acrylonitrile-butadiene oligomers; and

[0009] Component B comprises at least one catalyst.

[0010] According to a second aspect of the present invention, there is provided herein a method for preparing a two-component curable adhesive composition.

[0011] According to the third aspect of the present invention, there is provided a laminate comprising a first substrate, a second substrate and an adhesive layer sandwiched therebetween, wherein the first substrate and the second substrate are independently selected from glass, resin and metal, and the adhesive layer is formed by curing the adhesive composition of the present invention.

[0012] According to a fourth aspect of the present invention, there is provided an electronic device comprising the laminate of the present invention or a laminate prepared by using the adhesive composition of the present invention.

[0013] According to a fifth aspect of the present invention, there is provided herein a use of the adhesive composition according to the present invention or the laminate according to the present invention in manufacturing an electronic device.

[0014] Other features and aspects of the subject matter are described in greater detail below. DETAILED DESCRIPTION

[0015] It will be appreciated by those skilled in the art that the present invention is merely a description of an exemplary embodiment and is not intended to limit the broader aspects of the present invention. Each aspect so described may be combined with any one or more other aspects unless clearly indicated to the contrary. In particular, any feature indicated as being preferred or advantageous may be combined with any one or more other features indicated as being preferred or advantageous.

[0016] Unless otherwise stated, in the context of the present invention, the terms used are to be interpreted according to the following definitions.

[0017] As used herein, the terms "a," "an," "the," and "said" include both singular and plural referents unless otherwise specified.

[0018] As used herein, the terms "comprising" and "including" are synonymous with "containing" or "including", are inclusive or open-ended, and do not exclude additional, unrecited members, elements, or method steps.

[0019] The terms "at least one" or "one or more" used herein to qualify components refer to the type of component, rather than the absolute number of molecules.

[0020] As used herein, the term "copolymer" refers to a polymer having more than one monomer unit.

[0021] As used herein, the term "oligomer" refers to a low molecular weight polymer comprising 10 to 100 repeating units.

[0022] As used herein, the term "grafted polymer" refers to a polymer comprising molecules having one or more blocks attached to a main chain as side chains, these side chains having compositional or configurational characteristics different from those in the main chain.

[0023] The term "room temperature" as used herein refers to a temperature of about 15°C to about 35°C, preferably about 25°C.

[0024] Unless otherwise stated, the recitation of numerical endpoints includes all numbers and fractions subsumed within the corresponding range, as well as the recited endpoint.

[0025] The entire contents of all references cited in this specification are incorporated herein by reference.

[0026] Unless stated otherwise, molecular weights refer to weight-average molecular weight (Mw). Unless stated otherwise, all molecular weight data refer to the values ​​obtained by gel permeation chromatography (GPC), for example according to DIN 55672.

[0027] In this context, the glass transition temperature (Tg) or the melting point of a particular polymer is determined in accordance with DIN 53 765 using DSC.

[0028] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.

[0029] In one aspect, the present disclosure is generally directed to a two-component curable adhesive composition consisting of the following components:

[0030] Component A, comprising:

[0031] (a) at least one alkyl (meth)acrylate monomer,

[0032] (b) at least one acrylonitrile-butadiene rubber, wherein the acrylonitrile-butadiene rubber has an acrylonitrile content of less than 45% by weight, based on the total weight of the acrylonitrile-butadiene rubber, and

[0033] (c) at least one toughening agent selected from polyester-based urethane (meth)acrylate oligomers and / or (meth)acrylate-terminated acrylonitrile-butadiene oligomers; and

[0034] Component B comprises at least one catalyst.

[0035] Component A:

[0036] (a) Alkyl (meth)acrylate monomer

[0037] According to the present invention, component A comprises at least one alkyl (meth)acrylate monomer.

[0038] The alkyl (meth) acrylate monomer used for component A can be any alkyl ester of acrylic acid or methacrylic acid known in the art. Examples include esters of C1-C6 monofunctional alcohols with (meth) acrylic acid (e.g., methyl acrylate, methyl methacrylate, ethyl acrylate or ethyl methacrylate, n-propyl acrylate or isopropyl acrylate, or n-propyl methacrylate or isopropyl methacrylate, butyl (meth) acrylate (all isomers)) and hexyl (meth) acrylate, esters of higher molecular weight alcohols with no more than 12 carbon atoms (e.g., lauryl (meth) acrylate, 2-ethylhexyl (meth) acrylate, hexyl (meth) acrylate, isodecyl (meth) acrylate, etc.). Component A can also include a combination of two or more such monomers. Preferred alkyl (meth) acrylate monomers are esters of C1-C4 monofunctional alcohols with (meth) acrylic acid, and methacrylate is particularly preferred. Methyl methacrylate is particularly preferred.

[0039] Suitable commercially available components (a) may be methyl methacrylate from Lucite International, VISIOMER from Evonik TM MMA, and methyl methacrylate from Mitsubishi Chemical.

[0040] Particularly preferably, the alkyl (meth)acrylate monomer (a) may be present in an amount of 40 to 85 wt %, and preferably 40 to 70 wt %, based on the total weight of the adhesive composition.

[0041] (b) Acrylonitrile butadiene rubber

[0042] According to the invention, component A comprises at least one acrylonitrile-butadiene rubber, wherein the acrylonitrile-butadiene rubber has an acrylonitrile content of less than 45% by weight, based on the total weight of the acrylonitrile-butadiene rubber.

[0043] In the context of the present application, the term acrylonitrile-butadiene rubber (also known as nitrile rubber, also abbreviated as "NBR") should be understood to mean a rubber that is a copolymer, terpolymer or tetrapolymer of at least one α,β ethylenically unsaturated nitrile, at least one conjugated diene and optionally one or more additional copolymerizable monomers. Typically, the weight average molecular weight (Mw) of NBR is about 700,000 g / mol or higher than 700,000 g / mol.

[0044] Preferably, the acrylonitrile-butadiene rubber has an acrylonitrile content of 10 to 42 wt %, preferably 20 to 40 wt %, and more preferably 30 to 40 wt %, based on the total weight of the acrylonitrile-butadiene rubber. The higher the acrylonitrile content in the acrylonitrile-butadiene rubber, the higher the oil resistance, but the lower the flexibility of the material. By using such a specific range, the two-component curable adhesive composition has a balanced characteristic of chemical resistance and fluidity.

[0045] Functionalized acrylonitrile-butadiene rubber is a copolymer that has been chemically modified to contain one or more functional groups (e.g., hydroxyl, amino, ether, ester, amide, sulfonate, sulfonic acid, carboxyl or carboxylate groups), which can also be used as component (b). The presence of functional groups on the acrylonitrile-butadiene rubber can promote crosslinking. In one embodiment, the functionalized acrylonitrile-butadiene rubber contains one or more functional groups that are covalently bonded to the copolymer backbone directly or through a moiety (e.g., an alkyl).

[0046] Derivatives of NBR include carboxylated NBR (XNBR), carboxylated hydrogenated NBR (XHNBR), and NBR having some of the nitrile groups replaced with amide groups (referred to as amidated NBR or ANBR), or a combination comprising at least one of the foregoing.

[0047] In some embodiments, the acrylonitrile-butadiene rubber (b) has a glass transition temperature (Tg) of -15°C to -45°C, preferably -30°C to -35°C.

[0048] Acrylonitrile-butadiene rubbers suitable for component (b) can be prepared by free radical copolymerization of butadiene and acrylonitrile in emulsion.

[0049] Suitable commercially available acrylonitrile-butadiene rubbers are available from Zeon Chemicals as Nipol TM DN401L, DN2850, 1052 and 4050 for sale.

[0050] Particularly preferably, the acrylonitrile-butadiene rubber may be present in an amount of 0.1 to 30 wt %, and preferably 5 to 25 wt %, based on the total weight of the adhesive composition.

[0051] (c) Toughening agent

[0052] According to the present invention, component A comprises at least one toughening agent selected from polyester-based urethane (meth)acrylate oligomers and / or (meth)acrylate-terminated acrylonitrile-butadiene oligomers.

[0053] In some embodiments, a polyester-based urethane (meth) acrylate oligomer is used as a toughening agent in component A of the adhesive composition of the present invention. The polyester-based urethane (meth) acrylate oligomer may be selected from a monofunctional polyester-based urethane (meth) acrylate oligomer and / or a multifunctional polyester-based urethane (meth) acrylate oligomer, preferably a difunctional polyester-based urethane acrylate oligomer.

[0054] The polyester-based urethane (meth)acrylate oligomer may have a weight average molecular weight (Mw) of about 10,000 to about less than about 40,000 g / mol.

[0055] In some embodiments, the polyester-based urethane (meth) acrylate oligomer can be obtained by reacting a polyester polyol with an aliphatic or aromatic isocyanate having two or more isocyanate groups in one molecule and then subjecting the remaining unreacted isocyanate groups to an addition reaction with a hydroxyl-containing (meth) acrylate monomer. The polyester polyol used to prepare the polyester-based urethane (meth) acrylate oligomer can be selected from polyethylene adipate diol, polybutylene adipate diol, polyhexamethylene isophthalate adipate diol, 3-methyl-1,5-pentane isophthalate diol, 3-methyl-1,5-pentane terephthalate diol, and a condensate of 1,6-hexanediol and a dimer acid. The aliphatic or aromatic isocyanate having two or more isocyanate groups in one molecule for preparing the polyester-based urethane acrylate oligomer may be selected from: isophorone diisocyanate; dicyclohexylmethane-4,4-diisocyanate; hexamethylene diisocyanate; aliphatic isocyanate-based compounds including 2,2,4-trimethylhexane diisocyanate, butylene diisocyanate, 1,3-butadiene-1,4-diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, 1,6,11-undecane triisocyanate, and the like; and diisocyanate. (Isocyanatoethyl)benzene, bis(isocyanatopropyl)benzene, bis(isocyanatobutyl)benzene, bis(isocyanatomethyl)naphthalene, bis(isocyanatomethyl)diphenyl ether, phenylene diisocyanate, ethylphenylene diisocyanate, isopropylphenylene diisocyanate, dimethylphenylene diisocyanate, diisopropylphenylene diisocyanate, trimethylbenzene triisocyanate, benzene triisocyanate, biphenyl diisocyanate, 3,3-dimethoxybiphenyl-4,4-diisocyanate, hexahydrophenylene diisocyanate, hexahydrodiphenylmethane-4,4-diisocyanate, and mixtures thereof. The hydroxyl-containing (meth)acrylate monomer used to prepare the polyester-based urethane acrylate oligomer can be selected from 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 1-chloro-2-hydroxypropyl (meth)acrylate, diethylene glycol mono(meth)acrylate, 1,6-hexanediol mono(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate and combinations thereof.

[0056] Suitable commercially available polyester based urethane (meth)acrylate oligomers are sold as BR-7432GB and BR-741 by BOMAR Specialties LLC, as GENOMER 3485 and GENOMER 3611 by RAHN, and as UX-3204 and UXT-6000 by Nippon kayaku.

[0057] As an alternative, (meth)acrylate-terminated acrylonitrile-butadiene oligomers can also be used as toughening agents in component A of the adhesive composition of the present invention to achieve the desired effect. (Meth)acrylate-terminated acrylonitrile-butadiene oligomers refer to (meth)acrylate groups located at both ends of the main chain of the acrylonitrile-butadiene copolymer.

[0058] There is no limitation on the acrylonitrile content of the (meth)acrylate-terminated acrylonitrile-butadiene oligomers used in the present invention, for example, they may have an acrylonitrile content of 5 to 60% based on the total weight of the (meth)acrylate-terminated acrylonitrile-butadiene oligomers.

[0059] In a preferred embodiment, the (meth)acrylate-terminated acrylonitrile-butadiene oligomer may have a weight average molecular weight (Mw) of less than 200,000 g / mol, more preferably 3000 to 10000 g / mol.

[0060] In a preferred embodiment, the (meth)acrylate terminated acrylonitrile-butadiene oligomer may have a viscosity of 50,000 cps to 1,000,000 cps at ambient temperature.

[0061] Suitable commercially available (meth)acrylate terminated acrylonitrile-butadiene oligomers are available from Huntsman as Hypro TM 1300X33LC VTBNX and Hypro TM 1300X43LC VTBNX for sale.

[0062] In some embodiments, a combination of a polyester-based (meth)urethane acrylate oligomer and a (meth)acrylate-terminated acrylonitrile-butadiene oligomer may be used as a toughening agent in component A of the adhesive composition of the present invention.

[0063] Particularly preferably, the toughening agent (c) may be present in an amount of 0.1 to 20 wt %, and preferably 5 to 15 wt %, based on the total weight of the adhesive composition.

[0064] (d) a core-shell graft polymer different from component (b)

[0065] According to the present invention, component A optionally comprises at least one core-shell graft polymer different from component (b). Typically, component (d), if present, is non-reactive in the composition and serves to adjust the viscosity and to provide toughness to the adhesive composition when cured.

[0066] The core-shell graft polymer used for component (d) can be any of those familiar to those skilled in the art. These materials are particulate graft copolymers having a rubbery or elastomeric core and a hard shell. They swell in the alkyl (meth) acrylate monomer (a), but do not dissolve therein. Typically, so-called "hard" monomers (e.g., styrene, acrylonitrile, or methyl methacrylate) are grafted onto a rubbery core made from a polymer of so-called "soft" monomers (e.g., butadiene or ethyl acrylate). The "core" or backbone polymer of the grafted polymer has a glass transition temperature significantly below ambient temperature. The "shell" polymer grafted onto the backbone polymer has a glass transition temperature significantly above ambient temperature. Ambient temperature is defined as the temperature range in which the adhesive composition is used.

[0067] Core-shell polymers are usually referred to by the abbreviations of the monomers they contain, among which useful types are methacrylate-butadiene-styrene (MBS) graft copolymers, styrene-butadiene-styrene (SBS) graft copolymers, acrylate-styrene-acrylic acid (ASA) graft copolymers, acrylonitrile-butadiene-styrene graft copolymers (ABS) and combinations thereof.

[0068] Preferably, the core-shell graft polymer comprises a shell derived from a methacrylate polymer or copolymer.Core-shell graft polymers of the MBS type are preferred.

[0069] Suitable commercially available core-shell graft polymers are marketed by KANEKA BELGIUM NV as Kane Ace TM FM50 sold by KANEKA as KANE ACE TM M-521 and KANE ACE TM Sold as B-564 and by Mitsubishi Chemical as S-2030 and C-223A.

[0070] Particularly preferably, the core-shell graft polymer (d) may be present in an amount of 0.1 to 30 wt %, and preferably 5 to 20 wt %, based on the total weight of the adhesive composition.

[0071] additive

[0072] Component A may optionally include at least one additive selected from the group consisting of adhesion promoters, inhibitors, chelating agents, reducing agents, thixotropic agents, and combinations thereof.

[0073] Adhesion promoters can enhance the adhesion of the composition to the substrate. Suitable examples can be organic acids, carboxylic acids and methacrylated phosphates. Exemplary carboxylic acids include methacrylic acid, maleic acid, acrylic acid, fumaric acid, malonic acid and combinations thereof. Exemplary methacrylated phosphates include 2-hydroxyethyl methacrylate phosphate, phosphate esters of polyethylene glycol monomethacrylate, ethyl methacrylate phosphate and combinations thereof. Commercially available products of adhesion promoters can be obtained from Harcros Chemicals as Harcryl 1228. If present, the adhesion promoter can be present in an amount of 0.1 to 15 wt %, more preferably 0.1 to 10 wt %, based on the gross weight of the adhesive composition.

[0074] Reducing agents can act as catalysts. Suitable examples can be selected from tertiary amines and aldehyde amine reaction products. Available tertiary amines include N, N-dimethylaniline, N, N-dimethyltoluidine, N, N-dimethylaniline, p-tolyldiethanolamine and combinations thereof. Commercially available products of reducing agents (e.g., N, N-dimethyl-p-toluidine) can be obtained by RSA Corporation. If present, based on the gross weight of the adhesive composition, the reducing agent can be present in an amount of 0.5 to 5 wt %, more preferably 1 to 2 wt %.

[0075] Inhibitor can prolong the shelf life of adhesive composition and provide the desired working time. Suitable example is hydroquinone, methylhydroquinone, p-naphthoquinone and their combination. The commercially available product of inhibitor (for example methylhydroquinone) can be obtained from SigmaAldrich. If present, based on the gross weight of adhesive composition, inhibitor can exist with the amount of 0.01 to 1 % by weight, more preferably 0.01 to 0.1 % by weight.

[0076] A thixotropic agent can be used to adjust the viscosity of the adhesive composition. A suitable thixotropic agent is fumed silica. A commercially available product of fumed silica can be obtained from Evonik as Aerosil 200. If present, the thixotropic agent can be present in an amount of 0.1 to 5 wt %, more preferably 0.1 to 2 wt %, based on the gross weight of the adhesive composition.

[0077] Chelating agents can be used to chelate metal ions in the adhesive to prevent premature curing and improve storage stability. Suitable chelating agents can be ethylenediaminetetraacetic acid (EDTA). A commercially available product of chelating agents is Versene 220 from Dow. If present, the chelating agent can be present in an amount of 0.01 to 1 weight %, more preferably 0.01 to 0.5 weight %, based on the total weight of the adhesive composition.

[0078] Component B Catalyst

[0079] According to the invention, component B comprises at least one catalyst which is suitable for accelerating the curing and / or crosslinking of component A.

[0080] Suitable catalysts for use in the present invention include benzoyl peroxide, cumene hydroperoxide, tert-butyl hydroperoxide, dicumyl peroxide, tertiary butyl peroxide acetate, tertiary butyl perbenzoate, di-tert-butylazobisisobutyronitrile, and combinations thereof.

[0081] Particularly preferably, the catalyst may be present in an amount of 0.1 to 20 wt %, and preferably 1 to 10 wt %, based on the total weight of the adhesive composition.

[0082] Adhesive composition

[0083] The mixing ratio between component A and component B may be 1:1 to 20:1, preferably 4:1 to 10:1 by weight.

[0084] In a particularly preferred embodiment, the two-component curable adhesive composition comprises, based on the total weight of the adhesive composition:

[0085] 40 to 85 wt. %, preferably 40 to 70 wt. %, of at least one alkyl (meth)acrylate monomer (a);

[0086] 0.1 to 30% by weight, preferably 5 to 25% by weight, of at least one acrylonitrile-butadiene rubber (b), wherein the acrylonitrile-butadiene rubber has an acrylonitrile content of less than 45% by weight, based on the total weight of the acrylonitrile-butadiene rubber;

[0087] 0.1 to 20 wt%, preferably 5 to 15 wt% of a toughening agent (c), wherein the toughening agent is selected from polyester-based urethane (meth)acrylate oligomers or (meth)acrylate-terminated acrylonitrile-butadiene oligomers;

[0088] 0.1 to 30% by weight, preferably 5 to 20% by weight, of at least one core-shell graft polymer (d) which is different from component (b);

[0089] 0.1 to 15% by weight, preferably 0.1 to 10% by weight, of at least one adhesion promoter;

[0090] 0.5 to 5 wt %, more preferably 1 to 2 wt % of at least one reducing agent;

[0091] 0.01 to 1 wt %, more preferably 0.01 to 0.1 wt % of at least one inhibitor;

[0092] 0.1 to 5 wt. %, more preferably 0.1 to 2 wt. % of at least one thixotropic agent;

[0093] 0.01 to 1 wt %, more preferably 0.01 to 0.5 wt % of at least one chelating agent; and

[0094] 1 to 20% by weight of at least one catalyst.

[0095] Preparation method

[0096] The two-component curable adhesive composition according to the present invention can be prepared by the following steps to obtain the composition:

[0097] (i) adding inhibitors and chelating agents, if present, to component (a);

[0098] (ii) dissolving component (b) in the above mixture by mixing until a homogeneous solution is obtained;

[0099] (iii) adding component (d), if present, and stirring until a smooth paste is obtained;

[0100] (iv) adding component (c) and other additives if present to the above paste, and mixing until all components are dispersed to obtain component A; and

[0101] (v) The catalyst (component B) is prepared and stored separately and mixed with component A before use.

[0102] There is no particular restriction on the apparatus used for these mixing, stirring, dispersing, etc. An automatic mortar, a Henschel mixer, a three-roll mill, a ball mill, a planetary mixer, a bead mill, etc. equipped with a stirrer and a heater can be used. In addition, a suitable combination of these apparatuses can be used. There is no particular restriction on the preparation method of the two-component curable adhesive composition, as long as it is a composition in which the above components are uniformly mixed.

[0103] Laminates and electronic devices

[0104] According to the third aspect of the present invention, there is provided a laminate comprising a first substrate, a second substrate and an adhesive layer sandwiched therebetween, wherein the first substrate and the second substrate are independently selected from glass, resin and metal, and the adhesive layer is formed by curing the adhesive composition of the present invention.

[0105] The first substrate and / or the second substrate may be of a single material and a single layer, or may comprise multiple layers of the same or different materials. These layers may be continuous or discontinuous.

[0106] The substrates of the articles described herein can have a variety of properties, including rigidity (e.g., a rigid substrate, i.e., a substrate that cannot be bent by an individual using two hands, or that breaks if attempted to bend using two hands), flexibility (e.g., a flexible substrate, i.e., a substrate that can be bent using no more than two hands of force), porosity, conductivity, lack of conductivity, and combinations thereof.

[0107] The substrate of the article can be in a variety of forms including, for example, fibers, threads, yarns, woven fabrics, nonwovens, films (e.g., polymer films, metallized polymer films, continuous films, discontinuous films, and combinations thereof), foils (e.g., metal foils), sheets (e.g., metal sheets, polymer sheets, continuous sheets, discontinuous sheets, and combinations thereof), and combinations thereof.

[0108] In a preferred embodiment, at least one substrate may be selected from: metals, such as metalfiring paste, aluminum, tin, molybdenum, silver; conductive metal oxides, such as indium tin oxide (ITO), fluorine-doped tin oxide, aluminum-doped zinc oxide, etc.; glass, such as ink glass, bare glass; resins, such as polycarbonate, polybutylene terephthalate and polyamide. Other suitable metals include copper, gold, palladium, platinum, aluminum, indium, silver-plated copper, silver-plated aluminum, tin, and tin-plated copper. Preferably, both substrates are selected from one of the aforementioned materials.

[0109] The two-component curable adhesive composition of the present invention may be cured at room temperature ranging from 15° C. to 35° C. for 1 to 3 days.

[0110] As will be appreciated, the time and temperature cure profile of each two-component curable adhesive composition is different, and different compositions can be designed to provide a cure profile that will be suitable for a particular industrial manufacturing process.

[0111] According to a fourth aspect of the present invention, there is provided an electronic device comprising the laminate of the present invention or a laminate prepared by using the adhesive composition of the present invention.

[0112] The two-component curable adhesive composition of the present invention can be applied to the substrate using any suitable application method, including, for example, automatic fine line dispensing, jet dispensing, slot die coating, roller coating, gravure coating, transfer coating, pattern coating, screen printing, spraying, filament coating, by extrusion, air knife, trailing blade, brushing, dipping, scraper, offset gravure coating, rotary gravure coating, and combinations thereof. The two-component curable adhesive composition can be applied as a continuous or discontinuous coating, in a single layer or multiple layers, and combinations thereof.

[0113] use

[0114] According to a fifth aspect of the present invention, there is provided herein a use of the adhesive composition according to the present invention or the laminate according to the present invention in manufacturing an electronic device.

[0115] Suitable electronic devices include, but are not limited to, wearable electronic devices (e.g., watches and glasses), handheld electronic devices (e.g., phones (e.g., cellular phones and cellular smartphones), cameras, tablets, e-readers, monitors (e.g., in hospitals and for use by medical personnel, athletes, and individuals), watches, calculators, mice, touchpads, and joysticks), computers (e.g., desktop and laptop computers), computer monitors, televisions, media players, or other electronic components.

[0116] Example

[0117] The following examples are intended to help those skilled in the art better understand and practice the present invention. The scope of the present invention is not limited by the examples, but by the appended claims. Unless otherwise indicated, all parts and percentages are based on weight.

[0118] Raw materials:

[0119] Methyl methacrylate was obtained from Lucite International.

[0120] Nipol TM DN401L is an acrylonitrile-butadiene rubber having an acrylonitrile content of 19 wt. % available from Zeon.

[0121] Nipol TM DN2850 is an acrylonitrile-butadiene rubber having an acrylonitrile content of 28 wt. % available from Zeon.

[0122] Nipol TM 1052 is an acrylonitrile-butadiene rubber having an acrylonitrile content of 33 wt%, available from Zeon.

[0123] Nipol TM 4050 is an acrylonitrile-butadiene rubber having an acrylonitrile content of 40 wt. % available from Zeon.

[0124] Nipol TM 4580 is an acrylonitrile-butadiene rubber having an acrylonitrile content of 45 wt. % available from Zeon.

[0125] Hypro TM1300X33LC VTBNX is a methacrylate terminated acrylonitrile-butadiene oligomer available from Huntsman.

[0126] Hypro TM 2000X168LC is a methacrylate terminated polybutadiene available from Huntsman.

[0127] BR641D is a polybutadiene urethane acrylate oligomer available from BOMAR Specialties LLC.

[0128] BR204 is a polyether based urethane acrylate oligomer available from BOMAR Specialties LLC.

[0129] BR7432GB is a polyester based urethane acrylate oligomer available from BOMAR Specialties LLC.

[0130] Kane Ace TM FM50 is an acrylic core-shell polymer available from KANEKA BELGIUM NV.

[0131] Methacrylic acid is an adhesion promoter obtained from

[0132] Harcryl 1228 is an adhesion promoter available from Harcros Chemicals.

[0133] Methylhydroquinone was the inhibitor and was obtained from Sigma Aldrich.

[0134] VERSENE TM 220E is a chelating agent based on tetrasodium ethylenediaminetetraacetic acid tetrahydrate available from Dow.

[0135] N,N-Dimethyl-p-toluidine was the reducing agent and was obtained from RSA Corporation.

[0136] Aerosil 200 is fumed silica available from Evonik.

[0137] Perkabox GB-50 is 50% dibenzoyl peroxide in a phthalate-free carrier available from Nouryon.

[0138] Test method:

[0139] Viscosity:

[0140] The viscosity in the present invention is measured using a No. 27 spindle and a Brookfield viscometer within a temperature range of 25° C. A viscosity of less than 25,000 mPa·s is acceptable.

[0141] Stability test of component A:

[0142] After mixing all ingredients of Component A, the Examples and Comparative Examples were visually observed. If a homogeneous composition was observed, the Example was scored as "stable", otherwise it was scored as "phase separated". Only "stable" was acceptable.

[0143] Test sample preparation

[0144] Each test sample was made of two cleaned polyamine (PA) plastic sheets of different sizes (the dimensions of the large sheet with a hole in the middle were: 40 mm in width and length, and 3 mm in thickness; and the dimensions of the small sheet were: 30 mm in width and length, and 3 mm in thickness), glass beads with a diameter of 0.127 mm, and a two-component curable adhesive of the embodiments / comparative examples of the present invention.

[0145] First, the PA sheet was wiped and cleaned with isopropyl alcohol. The two-component curable composition was then mixed by a dispenser and a sufficient number of adhesive beads were dispensed around the hole on the large PA sheet so that a 275 mm diameter hole could be formed when joining another small PA sheet. 2 Then sprinkle some glass beads on the bonding line as a gap controller; then place a small PA sheet on the adhesive to ensure an effective bonding area of ​​275mm 2 , and remove excess adhesive around the hole; clamp the assembly until the adhesive cures for 24 hours at 23°C and 50% relative humidity.

[0146] Launch strength test

[0147] The push-out strength test is carried out using a universal testing machine with a punch at 23±2°C and 50%±5% relative humidity. The punch applies a compressive force on the small piece through the hole of the large piece, with a push-pull speed of 2mm / min until the assembly can no longer support the load. The maximum load is recorded, and the push-out strength is calculated by dividing the maximum load by the bonding area.

[0148] Oil acid resistance test

[0149] The test specimens were prepared as described above and cured for 24 hours, then 100% pure oleic acid was applied along the lap bond edges using a pipette, allowing capillary action to draw the oleic acid to the center of the specimen. The oleic acid should completely fill any voids around the adhesive. The specimens were then aged at 65°C and 90% relative humidity for 300 hours. The aged specimens were removed and placed at room temperature; after 2 hours, the aged specimens were used to test the push-out strength as described above.

[0150] Push-out strength retention

[0151] The retention rate was calculated according to the following equation:

[0152] Retention rate = (push-out strength after aging / push-out strength before aging)*100%.

[0153] Retention rates greater than 50% are acceptable, and greater than 70% are preferred.

[0154] Examples 1 to 12 (Ex. 1 to Ex. 12) and Comparative Examples 1 to 4 (CEx. 1 to CEx. 4)

[0155] Adhesives were prepared using the components in the amounts (parts by weight) listed in Tables 1 and 2 using the following method, test samples were prepared as described above, and properties were tested using the methods described above, and the evaluation results are shown in Tables 1 and 2.

[0156] Preparation method:

[0157] All embodiments and comparative examples were prepared by the following steps:

[0158] (i) adding an inhibitor and a chelating agent to an alkyl (meth)acrylate monomer (a);

[0159] (ii) dissolving acrylonitrile-butadiene rubber (b) in the above mixture by mixing until a uniform solution is obtained;

[0160] (iii) adding the core-shell graft polymer (d) and stirring until a smooth paste is obtained;

[0161] (iv) adding toughening agent (c) and other additives to the above paste and mixing until all components are dispersed, thereby obtaining component A; and

[0162] (v) Mix it with the catalyst (component B) before use.

[0163] Table 1

[0164]

[0165]

[0166] N / A means the test is not applicable because Component A exhibited phase separation.

[0167] Table 2

[0168]

[0169] Table 2

[0170]

[0171]

[0172] As can be seen from Tables 1 and 2, compositions having component (b) having an acrylonitrile content outside the claimed range or a toughening agent other than the present invention either have phase separation lacking processability or have unsatisfactory resistance to oleic acid chemicals.

[0173] Although some preferred embodiments have been described, many modifications and variations are possible in light of the above teachings. It is therefore to be understood that the invention may be practiced otherwise than as specifically described without departing from the scope of the appended claims.

Claims

1. A two-component curable adhesive composition consisting of the following components: Component A, comprising: (a) at least one alkyl (meth)acrylate monomer, (b) at least one acrylonitrile-butadiene rubber, wherein the acrylonitrile-butadiene rubber has an acrylonitrile content of less than 45% by weight, based on the total weight of the acrylonitrile-butadiene rubber, and (c) at least one toughening agent selected from polyester-based urethane (meth)acrylate oligomers and / or (meth)acrylate-terminated acrylonitrile-butadiene oligomers; and Component B comprises at least one catalyst.

2. The two-component curable adhesive composition according to claim 1, wherein the composition optionally comprises (d) at least one core-shell graft polymer different from component (b).

3. A two-component curable adhesive composition according to claim 1 or 2, wherein the at least one alkyl (meth)acrylate monomer (a) is selected from esters of C1-C6 monofunctional alcohols and (meth)acrylic acid, preferably methyl acrylate, methyl methacrylate, ethyl acrylate or ethyl methacrylate, n-propyl acrylate or isopropyl acrylate, or n-propyl methacrylate or isopropyl methacrylate, butyl (meth)acrylate (all isomers) and hexyl (meth)acrylate; esters of higher molecular weight alcohols having not more than 12 carbon atoms, preferably lauryl (meth)acrylate, 2-ethylhexyl (meth)acrylate, hexyl (meth)acrylate, isodecyl (meth)acrylate, etc.; more preferably esters of C1-C4 monofunctional alcohols and (meth)acrylic acid; even more preferably methyl methacrylate.

4. The two-component curable adhesive composition according to any one of the preceding claims, wherein the acrylonitrile-butadiene rubber (b) has an acrylonitrile content of 10 to 42 wt%, preferably 20 to 40 wt%, and more preferably 30 to 40 wt%, based on the total weight of the acrylonitrile-butadiene rubber.

5. The two-component curable adhesive composition according to any one of the preceding claims, wherein the acrylonitrile-butadiene rubber (b) has a glass transition temperature (Tg) of -15°C to -45°C, preferably -30°C to -35°C.

6. The two-component curable adhesive composition according to any one of the preceding claims, wherein the at least one toughening agent (c) has a molecular weight of less than 200,000 g / mol.

7. The two-component curable adhesive composition according to any one of the preceding claims, wherein the polyester-based urethane (meth)acrylate oligomer is selected from monofunctional polyester-based urethane (meth)acrylate oligomers and / or multifunctional polyester-based urethane (meth)acrylate oligomers, preferably difunctional polyester-based urethane acrylate oligomers.

8. The two-component curable adhesive composition according to any one of the preceding claims, wherein the polyester-based urethane (meth)acrylate oligomer has a weight average molecular weight (Mw) of 10,000 to less than 40,000 g / mol.

9. The two-component curable adhesive composition according to any one of the preceding claims, wherein the core-shell graft polymer (d) is selected from methacrylate-butadiene-styrene (MBS) graft copolymers, styrene-butadiene-styrene (SBS) graft copolymers, acrylate-styrene-acrylic acid (ASA) graft copolymers, acrylonitrile-butadiene-styrene graft copolymers (ABS) and combinations thereof.

10. The two-component curable adhesive composition according to any one of the preceding claims, wherein the component A further comprises an additive selected from the group consisting of adhesion promoters, inhibitors, chelating agents, reducing agents, thixotropic agents, and combinations thereof.

11. A two-component curable adhesive composition according to any one of the preceding claims, wherein the catalyst in component B is selected from benzoyl peroxide, cumene hydroperoxide, tert-butyl hydroperoxide, dicumyl peroxide, tert-butyl peroxyacetate, tert-butyl perbenzoate, di-tert-butylazobisisobutyronitrile and combinations thereof.

12. A method for preparing a two-component curable adhesive composition according to any one of claims 1 to 11, comprising the following steps: (i) adding inhibitors and chelating agents, if present, to component (a); (ii) dissolving component (b) in the above mixture by mixing until a homogeneous solution is obtained; (iii) adding component (d), if present, and stirring until a smooth paste is obtained; (iv) adding component (c) and other additives if present to the above paste and mixing until all components are dispersed to obtain component A; and (v) The catalyst (component B) is prepared and stored separately and mixed with component A before use.

13. A laminate comprising a first substrate, a second substrate and an adhesive layer sandwiched therebetween, wherein the first substrate and the second substrate are independently selected from glass, resin and metal, and the adhesive layer is formed by curing the adhesive composition according to any one of claims 1 to 11.

14. An electronic device comprising the laminate according to claim 13 or a laminate prepared by using the adhesive composition according to any one of claims 1 to 11.

15. Use of the adhesive composition according to any one of claims 1 to 11 or the laminate according to claim 13 in the manufacture of electronic devices.

Citation Information

Patent Citations

  • Adhesive compositions and jointing method

    EP2194105B1

  • Composition for structural adhesive

    US20130292054A1

  • Adhesives for bonding composites

    US6602958B2